Digital-Based Civics Learning in Strengthening Democratic Characters of Digital Native Students - Meiwatizal Trihastuti (STAI Hubbulwathan Duri, 2022)
Civics learning as the executor of 21st century learning is evidence of the transformation of scientific progress and the renewal of the implementation of education. Civics learning is required to be able to increase student learning participation in its digital-based learning environment. Therefore, Civics teachers must not forget their duties as a medium to create skilled and intelligent young citizens by the character of their nation. This study examined the application of Civics learning applied through digital learning in strengthening the democratic character of digital native students. This study used literature study method by involving studies related to the research theme. The results of this study indicated that 1) Civics teachers used a scientific learning model to support the application of digital-based Civics learning, 2) Digital-based Civics learning could be a means for students to strengthen their democratic character, and 3) Digital-based Civics learning could increase student learning participation. Therefore, digital-based Civics Learning was able to develop a vision of 21st century learning in the application of learning that had educational and generative values and could develop the skills of citizens according to the character of the nations.